Influence of gestagens used in hormonal replacement therapy on the secretion of GIP, GLP-1 in postmenopausal women - Rogatko, Iwona; Milewicz, Tomasz; Krzysiek, Józef; Sztefko, Krystyna (Menopause Review/Przegląd Menopauzalny, 2010)
Aim of the study : To evaluate GIP and GLP-1 secretion in postmenopausal women on the HRT in relation to gestagen used. Material and method : 105 postmenopausal women (mean age 59.0 ±3.4 years) were included in the study. Group I (n = 32) consisted of women treated with oral dydrogesterone and transdermal 17-b- estradiol. Group II (n = 30) was treated with 17-b-estradiol and dydrogesterone orally. Group III (n = 15) received 17-b-estradiol transdermally and medroxyprogesterone orally. Women from group IV (n = 10) received 17-b-estradiol and noretisterone orally. Blood was taken twice – before and 60 min. after the meal - to the chilled tubes with EDTA and aprotinin. Such a protocol was used before the HRT began and in the 6th month of the HRT. Results : The HRT resulted in diminished plasma concentration of GIP and GLP-1 in both group I and II – before and after the meal (p < 0.05). In group III the same tendency in GIP levels was observed but the differences were not statistically significant. The GLP-1 concentrations were not affected by HRT, as well as GIP and GLP-1 levels in group IV. Conclusion : The plasma concentration of incretins (GIP and GLP-1) depends on the route of HRT delivery and on the kind of gestagen used.